Preparation of La0.7Ca0.3Mn0.95Fe0.05O3 perovskites by different methods: Catalytic activity towards the hydroxylation of benzene - Hanafy, Ahmed Imam; Ali, Ibraheem Othman; El-Bahy, Zeinhom Mohamed; Mahmoud, Khaled Hussein (European Journal of Chemistry, 2013)
Nanoparticles of the La0.7Ca0.3Mn0.95Fe0.05O3 perovskites were synthesized by various wet chemical routes, namely, co-precipitation, oxalate-gel and citrate-gel methods. Phase formation and crystal structure of the synthesized powders were examined by the X-ray diffraction (XRD). The morphology was evaluated by the scan electron microscopy (SEM). Infrared transmission spectroscopy revealed that stretching and bending modes were influenced by the preparation methods. The citrate gel method yielded better powder properties. The prepared perovskite samples were used in the oxidation of benzene. The highest activity for the catalytic oxidation of benzene to phenol in presence of hydrogen peroxide (H2O2) was obtained with the citrate-gel prepared sample.